Napier grass stunt disease prevalence, incidence, severity and genetic variability of the associated phytoplasma in Uganda - Kawube, Geofrey; Talwana, Herbert; Nicolaisen, Mogens; Alicai, Titus; Otim, Michael; Kabirizi, Jolly; Mukwaya, Anthony; Nielsen, Steen Lykke (Crop Protection, 2015)
The prevalence, incidence and severity of Napier grass stunt disease (NGSD) caused by phytoplasma on Pennisetum purpureum, the main fodder for livestock under intensive and semi-intensive management systems in Uganda were determined following a field survey carried out in 17 districts. A total of 298 Napier grass fields were visited and NGSD status visually assessed and 1192 samples collected for identification and confirmation of the phytoplasma by polymerase chain reaction (PCR) assays using universal primers P1/P6 nested with R16F2n/R16R2n and, tuf primers 890/340 nested with 835 and 400. From these, 221 PCR products were sequenced and sequences aligned. Napier grass stunt disease is widely spread at an epidemic proportion, with the districts at different risk levels. The most affected districts are in central, East and North parts of the country while those in the west are least affected. Sequence alignments and Blast searches showed that the phytoplasma causing NGSD in Uganda belonged to the phytoplasma group 16SrXI, with single nucleotide sequence variants in a few districts. Therefore, there is a need for development of an area wide NGSD management strategy to contain the disease.
Keywords: Epidemic; PCR; Pennisetum purpureum; Risk; tuf; Variant